Treatment of Unilateral PA by Adrenalectomy: Potential Reasons for Incomplete Biochemical Cure - Yang, Yuhong; Reincke, Martin; Williams, Tracy Ann (Experimental and Clinical Endocrinology & Diabetes, 2019)
The importance of an early diagnosis and appropriate management of patients with primary aldosteronism (PA) has become increasingly clear because of the adverse impact of the disorder on cardiovascular and cerebrovascular events and target organ damage. Adrenalectomy potentially cures patients with unilateral PA resulting in normalisation of blood pressure or significant clinical improvements in the majority of patients. Different criteria have been used to evaluate outcomes of unilateral adrenalectomy. Clinical remission (cure of hypertension) is observed in 6% to 86% of patients and clinical benefits from surgery are seen in the majority. Several factors have been identified that predict clinical success after surgery such as age, sex, anti-hypertensive medication dosage and known duration of hypertension. Biochemical remission of PA after unilateral adrenalectomy, characterised by the resolution of hyperaldosteronism and correction of pre-surgical hypokalaemia, is observed in 67% to 100% of patients with unilateral PA. In only a small proportion of patients, adrenalectomy fails to resolve hyperaldosteronism and inappropriate aldosterone production persists after surgery. In this review we discuss the potential reasons for failing to cure hyperaldosteronism after unilateral adrenalectomy for unilateral primary aldosteronism.
Keywords: Primary aldosteronism; adrenalectomy; aldosterone-producing adenoma; bilateral adrenal hyperplasia; persistent hyperaldosteronism